Effectiveness of the baby-friendly community initiative in promoting exclusive breastfeeding among HIV negative and positive mothers: a randomized controlled trial in Koibatek Sub-County, Baringo, Kenya - Betty Mogesi Samburu; Sera Lewise Young; Frederick Murunga Wekesah; Milkah Njeri Wanjohi; Judith Kimiywe; Peter Muriuki; Paula L. Griffiths; Stephen T. McGarvey; Nyovani Janet Madise; Elizabeth W. Kimani-Murage (International Breastfeeding Journal, 2020)
Abstract Background Although the baby-friendly community initiative (BFCI) has been proposed as a community-level approach to improve infant feeding practices, there is little data on its variation in effectiveness by HIV status. We conducted a study to determine the effectiveness of BFCI in changing knowledge and attitudes towards exclusive breastfeeding (EBF) and increasing the rates among HIV negative and HIV positive women in rural Kenya. Methods A community-based cluster-randomized controlled trial was implemented from April 2015 to December 2016 among 901 women enrolled across 13 clusters. The intervention groups received a minimum of 12 personalized home-based counselling sessions on infant feeding by trained community health volunteers from their first or second trimester of pregnancy until 6 months postpartum. Other interventions included education sessions at maternal child clinics, mother-to-mother support group meetings and bi-monthly baby-friendly gatherings targeting influencers. The control group received standard health education at the facility and during monthly routine home visits by community health volunteers not trained on BFCI. Primary outcome measures were the rates of EBF at week 1, months 2, 4 and 6 postpartum. Secondary outcomes included knowledge and attitudes regarding breastfeeding for HIV-exposed infants. Statistical methods included analysis of covariance and logistic regression. Results At 6 months, EBF rates among HIV negative mothers were significantly higher in the BFCI intervention arm compared to the control arm (81.7% versus 42.2% p = 0.001). HIV positive mothers in the intervention arm had higher EBF rates at 6 months than the control but the difference was not statistically significant (81.8% versus 58.4%; p = 0.504). In HIV negative group, there was greater knowledge regarding EBF for HIV-exposed infants in the intervention arm than in the control (92.1% versus 60.7% p = 0.001). Among HIV positive mothers, such knowledge was high among both the intervention and control groups (96% versus 100%, p > 0.1). HIV negative and positive mothers in the intervention arm had more favourable attitudes regarding EBF for HIV-exposed infants than the control (84.5% versus 62.1%, p = 0.001) and (94.6% versus 53.8% to p = 0.001) respectively. Conclusions BFCI interventions can complement facility-based interventions to improve exclusive and continued breastfeeding knowledge, attitudes, and behaviours among HIV negative and positive women.